Gaya Bahasa Satire dalam Talkshow Mata Najwa “Jenaka di Negeri Opera” - Titin Azhari; Hermandra Hermandra; Elvrin Septyanti (Departement of Mathematics Education, 2023)
This study aims to describe the form of satirical language style used by the interviewees in Mata Najwa's talk show